Drinking Water Quality Characterization and Heavy Metal Analysis in Springs of Dewan Gorah, District Palandri, Azad Jammu and Kashmir, Pakistan¤ - Asma Jamil; Tahseenullah Khan; Fahad Majeed; Danial Zahid; Zaibullah (International Journal of Economic and Environmental Geology, 2018)
In this study, water quality and microbial characterizations of fresh water springs of union council Dewangorah, Palandri, AJK have been studied. Sampling was done from January to October 2017, from fifteen different locations of study area, which are a drinking water source for natives of the area. Water samples were collected in sterilized glass bottles for physicochemical and microbial analysis and in clean plastic bottles for heavy metals analysis from various locations. Various physiochemical parameters including pH, Total dissolved solids (TDS), Conductivity, Chlorides (Cl-), Fluorides (F-), Chemical Oxygen Demand (COD), hardness and alkalinity were measured by standard methods. Heavy metals concentrations including Arsenic (As), Chromium (Cr), Copper (Cu), Iron (Fe), Lead (Pb) and Nickel (Ni) were evaluated using atomic absorption spectroscopy. It was found that concentration of Pb and Cr were above permissible limits of WHO at all locations. Standard plate count (SPC) was used to determine total viable count and total coliform counts in water samples. Various bacterial colonies were isolated from water samples and characterized by performing different biochemical tests including Gram staining, Catalase, Oxidase and Citrate utilization tests. Results showed that various physicochemical parameter such as pH, TDS, Cl-, F-, COD and heavy metals including As, Cu, Fe were within World Health Organization (WHO) standards. While values for conductivity of few samples were above permissible limits of WHO. The calculations for human health risk showed that heavy metals at present levels are not posing a threat to the population. Microbial analysis showed that water samples contain different pathogenic bacteria like E. coli, Salmolella spp., shigella spp etc. and are not fit for drinking purposes. The quality of drinking water of Dewangorah must be monitored by regulatory authorities and further research is required to identify the sources of water contamination and its mitigation.